Oxygen‐sensing mechanisms in cells. (10th June 2020) - Wilson, James W.; Shakir, Dilem; Batie, Michael; Frost, Mark; Rocha, Sonia
Abstract : The importance of oxygen for the survival of multicellular and aerobic organisms is well established and documented. Over the years, increased knowledge of its use for bioenergetics has placed oxygen at the centre of research on mitochondria and ATP‐generating processes. Understanding the molecular mechanisms governing cellular oxygen sensing and response has allowed for the discovery of novel pathways oxygen is involved in, culminating with the award of the Nobel Prize for Medicine and Physiology in 2019 to the pioneers of this field, Greg Semenza, Peter Ratcliffe and William Kaelin. However, it is now beginning to be appreciated that oxygen can be a signalling molecule involved in a vast array of molecular processes, most of which impinge on gene expression control. This review will focus on the knowns and unknowns of oxygen as a signalling molecule, highlighting the role of 2‐oxoglutarate‐dependent dioxygenases as central players in the cellular response to deviations in oxygen tension. Abstract : Understanding the molecular mechanisms governing cellular oxygen sensing and response has allowed for the discovery of novel pathways oxygen is involved in. Oxygen can be a signalling molecule involved in a vast array of molecular processes, most of which impinge on gene expression control. These include control of HIF, regulation of chromatin and transcription, regulation of cell fate and translation.